Histology, Histochemistry and Scanning Electron Microscopy of Tonsil of the Soft Palate of Buffalo (Bubalas bubalis) - Girgiri, Ibrahim Alhaji (Indian Journal of Veterinary Anatomy, 2018)
The tonsils of the soft palate were collected from 12 local mixed breed of adult buffaloes and were studied by light and electron microscopy. The mucosal surface of these tonsils was lined by stratified squamous non-keratinized tokeratinized epithelium. The stratified squamous non-keratinized epithelium, presented the stratum basale, stratum spinosum and the stratum superficiale and was modified into reticular epithelium where the underlying lymphoid tissue was observed. The propria submucosa having loose irregular connective tissue comprising of collagen, reticular and elastic fibres, lymphoid tissue and clusters of mucous glandular tissue and their ducts. The homogenous layer just below the stratified squamous non-keratinized to keratinized epithelium was weakly PAS positive. The mucous acini were strongly PAS positive for glycogen, acidic mucopolysaccharides, weakly sulfated mucosubstances, mucin and presence of more than 4% cysteine. Scanning electron microscopy of the mucosa presented folds and groove of varying shapes, delineated squamous cells, varying pattern of microplicae and openings of irregular placed glandular ducts.